Difficulties of Equality Education in the Sumatera Area - Wirdatul Aini (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2019)
This research is motivated by the role of Pendidikan Kesetaraan Kejar Paket (A, B, and C) in completing the 9-year compulsory education. However, in the implementation of the Kejar Paket there are still many problems faced. The research objective was to describe the difficulty of implementing Kejar Paket in North Sumatra, West Sumatra, and South Sumatra. Expost facto descriptive research type. The population of the study was that all subjects involved in the Kejar Paket were study residents, tutors, managers in three research locations. Samples were taken purposively for each study location. Data collection techniques are interviews, and the tools are interview guidelines. Data is processed in a quantitative descriptive manner. The research findings illustrate the low interest in learning as seen in the presence of learning citizens. Some tutors are recruited from Strata I and graduated from high school, so the learning approach is felt to be incompatible with learning in education outside school. Facilities and infrastructure used to use what is available at the venue for the activities. Some managers have not been so serious in managing learning activities. Learning materials for learning citizens are often too late for the study schedule, so tutors find it difficult to provide material to the learning community. Funding for learning activities is felt to be lacking. The standard of assessment to the learning community is felt to be very high, while the material provided has not supported the achievement of the expected results.